PENGEMBANGAN LEMBAR KERJA SISWA (LKS) BERBASIS HIGHER ORDER THINKING SKILL (HOTS) MATERI SEGITIGA PADA KELAS VII SMP NEGERI SUKARAYA - Ema Lidia; As Elly; Nur Fitriyana (JOURNAL of MATHEMATICS SCIENCE and EDUCATION, 2021)
This study aims to develop student worksheets based on HOTS on the triangular material for class VII in accordance with the 2013 curriculum which is valid and practical. This research is a development research using a 4-D development model which consists of 4 stages, namely: define, design, develop, and desiminate stages. The dessiminate stage was not carried out due to time constraints in the study. Based on the results of research analysis by the three experts, namely: linguists, media experts, and material experts, it shows that the HOTS-based student worksheet on triangle material meets the valid criteria with an average score of 3.33 and for the one to one trial, an average score is obtained. an average of 3.39. While the results of the analysis of the student practicality sheet consisting of 6 students, it was found that the HOTS-based student worksheet on the triangle material met the very practical criteria with an average score of 3.70 and for the practicality test the teacher obtained an average score of 3.76, it means that the HOTS-based student worksheet on the triangle material meets the valid criteria and is very practical.